(untitled) (REMUNOM, 2024)
Dispensing medications is one of the main duties of the pharmaceutical professional. Currently, there is a high number of dispensings of psychotropic medications, including: Clonazepam, Methylphenidate, and Ritalin. This study aimed to perform a retrospective analysis of the dispensing of psychotropic medications in a drugstore in the city of Itacoatiara from April to September 2024. The results attest to a significant increase in the use of psychotropic medications in the city of Itacoatiara. It is concluded that the presence of the Pharmacist is essential in the dispensing of psychotropic medications.